THE GEOLOGY OF THE SOUTHEASTERN BALTIC SEA: A REVIEW - Usaityte D. (My University, 2000)
The Baltic Sea, particularly its southeastern part, is discussed in the paper. Investigations of regional character as well as specialized studies in the area are reviewed. General historical works are mentioned briefly. Previous surveys since the 1950s are presented by the subject studied. The compilation of geological structure of the SE Baltic Sea bottom and adjacent land of Balticum (Baltic States: Estonia, Latvia, Lithuania) is based on considerable amounts of summarized materials. The crystalline basement, sedimentary cover and Quaternary deposits are characterized in the comprehensive survey of geological structure. From a stratigraphical point of view, geological sequence of the platformal cover is comparatively complete: deposits of all geological systems (from the Archean to Cenozoic) are present in the Baltic Syneclise. Considering geotectonical cycles, the sedimentary cover of the syneclise is subdivided into four structural complexes. The thickness and distribution of Quaternary deposits are closely related to the recent bottom relief of the Baltic Sea that in turn is inherited from the Pre-Quaternary surface. Buried palaeo-valleys are characteristic of the Pre-Quaternary surface in the Baltic region and the Baltic Sea bottom. The Quaternary is characterized by layers of various geneses and by sharp changes of their thicknesses.
Keywords: Archean; Cenozoic; Quaternary; Кайнозой::Четвертичная; Кайнозой; Cenozoic::Quaternary; Cenozoic; Precambrian::Archean; Докембрий::Архей